Friendly City, Friendly Urban Space: Public Open Space Integration to Urban Settlement (International Journal of Architecture and Urbanism, 2025)
One of the features of a friendly city is the existence of public open spaces. Cities in Indonesia, particularly North Sumatra Province, do not have many good quality public open spaces on a residential scale. This paper aims to explore the criteria and strategies for planning and designing public open spaces that are integrated with the residential environment. This paper consists of three parts. The first part will review the results of research on public open spaces that the author has done in the period 2012 to 2022. The second part describes problems related to public open spaces and settlements, especially in urban areas, with special note on post-pandemic conditions. The final section contains the author's ideas regarding the integration of public open space in settlements, especially in cities in developing countries such as Indonesia. The ideas proposed in this writing would be the basic for implementing a more responsive public open space in a city that lack of urban design tradition.